A cross-sectional study among medical professionals regarding willingness to work amid COVID-19 outbreak - Mishra, Sandhya; Shrivastava, Ankur; Kumar, Vijay; Chandra, Anamika; Rizvi, Jaun Zeb (International Journal Of Community Medicine And Public Health, 2021)
Background: On January 30, 2020, the World Health Organization declared the COVID-19 outbreak a global health emergency. With nearly 25000 fresh cases registered daily, the COVID-19 tally in India rose to 13 lakh till mid of July 2020, according to the Ministry of Health and Family Welfare. Understanding the inclination of doctors to work in COVID-19 outbreak is essential for betterment of health care services. Objective were to assess the willingness of Doctors to work in COVID-19 outbreak and to determine the factors affecting willingness to work in COVID-19 outbreak. Methods: The study was conducted among doctors working in various medical colleges, specialist hospitals and research centers across various states of India. A predesigned self-administered questionnaire in Google form was emailed to the participants. Data was collected and analysed using SPSS version 13. Results: Out of 342 participants, 61% were willing to work in the COVID-19 pandemic. Female participants and those staying with their family were found to be significantly more afraid of COVID-19 pandemic and also willingness to work was significantly lower among them than their male counterparts living away from family. Conclusions: The COVID-19 pandemic caused emotional distress among the doctors. However our results suggest that during an outbreak majority of doctors are willing to work and will be available in the future. Staying with family drives them away from work more due to fear of infection or death of their family members.